EFEKTIVITAS MINUMAN JAHE PUTIH (ZINGBER OFFICINALE VAR.AMARUM) TERHADAP MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER I DI PMB AI - Lestari, Wiwin (Midwifery And Complementary Care, 2024)
Background: Nausea and vomiting (emesis gravidarum) is a condition of nausea and vomiting commonly found in pregnant women that appears in the first trimester of pregnancy, namely the second or eighth week after conception. One of the efforts to overcome nausea and vomiting is non-pharmacological therapy, for example giving white ginger drink which contains gingerol which has anti-nausea and vomiting properties. Objective:. To determine the effectiveness of white ginger drink (Zingber officinale var.amarum) in reducing nausea and vomiting in first trimester pregnant women at PMB Aulia Insani. Methods: His type of research uses Quasy Experimental with Pre Posttest with Control Design. In this design, it was divided into two groups, namely the control group (not given white ginger drink) and the treatment group (given white ginger drink) before the treatment was given, previously the sample was given a pretest and after the experiment the sample was given a posttest.Result: There is effectiveness of white ginger drink in reducing nausea and vomiting in first trimester pregnant women, because white ginger contains shogaol and gingerol compounds which can act as anti-nauseaConclusion: There is effectiveness of white ginger drink in reducing nausea and vomiting in first trimester pregnant women, because white ginger contains shogaol and gingerol compounds which can act as anti-nauseaKeywords: White ginger drink, nausea and vomiting, first trimester pregnant women.